FDA Supplemental Approval Summary: Lenvatinib for the Treatment of Unresectable Hepatocellular Carcinoma. (10th November 2020) - Nair, Abhilasha; Reece, Kelie; Donoghue, Martha B.; Yuan, Weishi (Vivian); Rodriguez, Lisa; Keegan, Patricia; Pazdur, Richard
Abstract: : On August 16, 2018, the U.S. Food and Drug Administration approved lenvatinib (Lenvima, Eisai Inc.) for first‐line treatment of patients with unresectable hepatocellular carcinoma (HCC). Approval was based on an international, multicenter, randomized, open‐label, noninferiority trial (REFLECT; NCT01761266) conducted in 954 patients with previously untreated metastatic or unresectable HCC. Patients were randomized (1:1) to receive lenvatinib (12 mg orally once daily for patients with a baseline body weight ≥60 kg and 8 mg orally once daily for patients with a baseline body weight <60 kg) or sorafenib (400 mg orally twice daily) until radiological disease progression or unacceptable toxicity. REFLECT demonstrated that lenvatinib was noninferior but not statistically superior to sorafenib for overall survival (OS; hazard ratio, [HR] 0.92; 95% confidence intervals [CI], 0.79–1.06), with median OS of 13.6 and 12.3 months in the lenvatinib and sorafenib arms, respectively. REFLECT also demonstrated statistically significant improvements in investigator‐assessed progression‐free survival (PFS; HR, 0.66; 95% CI, 0.57–0.77]; p < 0.001), corresponding to median PFS of 7.4 and 3.7 months and overall response rate of 24.1% vs 9.2% per modified RECIST for HCC (mRECIST) in the lenvatinib and sorafenib arms, respectively. Consistent results were observed by an independent review facility per RECISTv1.1 and per mRECIST. The most common adverse reactions observed in the lenvatinib‐treated patients (≥20%) in decreasing frequency were hypertension, fatigue, diarrhea, decreased appetite, arthralgia/myalgia, decreased weight, abdominal pain, palmar‐plantar erythrodysesthesia syndrome, proteinuria, dysphonia, hemorrhagic events, hypothyroidism, and nausea. Implications for Practice: This article describes the U.S. Food and Drug Administration's review of data from a single trial, REFLECT, that supported the approval of lenvatinib, as a single agent, for the first‐line treatment of unresectable hepatocellular carcinoma (HCC). REFLECT was an open‐label, noninferiority trial that randomized 954 patients with HCC who were ineligible for liver‐directed therapy with no prior systemic therapy for HCC to lenvatinib or sorafenib. REFLECT demonstrated that lenvatinib‐treated patients had similar survival, more responses, and longer time to progression than those receiving sorafenib. Serious side effects were more common among lenvatinib‐treated patients. Lenvatinib is an effective treatment for patients with previously untreated HCC. Abstract : This article reviews the data and basis for FDA approval of lenvatinib for the first‐line treatment of patients with unresectable hepatocellular carcinoma.